Conflict formation and transformation in Indonesia: Chinese and indigenous Indonesians on their way to peace? : A peace and conflict analysis according to the Transcend method - Eifert, Yvonne; Justus Liebig University Giessen (My University, 2012)
The fall of the Indonesian President Soeharto in May 1998 which defined the end of his long reign (1966 1998) was marked by severe riots against the country s ethnic Chinese minority. These violent acts were not the first of their kind, but rather followed a pattern of ongoing conflict between indigenous Indonesians and ethnic Chinese that can be traced back to colonial times. Even till today the conflict remains unresolved and by default ethnic Chinese remain victims of its violence. An analysis of the conflict regarding its forms of violence, conflict content, conflict structures and transformation potential will be conducted here along with the following research questions: what is the conflict between the ethnic Chinese and the indigenous Indonesians about? What are the underlying structures causing frictions between the two groups which initiate violent conflict? How can this conflict be transformed into the direction of sustainable peace acceptable to all parties involved?The present analysis is conducted according to the Transcend theory and method for conflict transformation developed by peace and conflict researcher Johan Galtung. This method is primarily applied by mediators out in the field and rarely for conflict studies in academic research. Here, the method is thereby tested on this specific case study in order to prove its application in the realm of peace and conflict studies. Within this thesis not only relevant literature, but also expert interviews conducted by the author during 2008 and 2010 in Indonesia are taken into consideration. The historical development of the conflict until the Soeharto regime shows that the Dutch as the ruling colonial power deliberately created a social system in which the ethnic Chinese have been positioned between the Dutch elite and the indigenous majority population as marginalized outsiders. How violence developed and if it still exists is assessed according to the triangle of violence , an analytic tool developed by Galtung. From 1998 onwards the quantity of violence shifted: acts of violence directed against ethnic Chinese and their properties as well as state-led discrimination have reduced significantly, nevertheless, ethnic Chinese continue to be discriminated against within their daily life. Post-Soeharto governments abolished discriminatory laws enabling ethnic Chinese to openly live and display their cultural identity; however, on the regional level respective laws are still in place or have been revived. To develop conflict transformation approaches for this conflict, it has been further analyzed utilising Galtung s analytic tools the triangle of conflict and the deep dimension conflict triangle . In the case of the triangle of conflict , the actors are not portrayed as monolithic blocks, but in subgroups. Within both main conflict groups, different subgroups have been detected who have interests and attitudes that transcend the ethnic division between the major groups. Among both conflict groups, these subgroups have a vested interest in maintaining the social status quo in which the ethnic Chinese live as marginalized outsiders. Other more conciliatory subgroups are in favor of significant social change and individuals from these groups have already paved the way for comprehensive conflict transformation by having initiated diverse projects which tackle the conflict from various angles. The analysis of the conflict s deep dimensions reveals aspects which go beyond the conflict formation itself: cultural backgrounds that subconsciously influence conflict actors and associated conflict infrastructure. The cultural background of indigenous Indonesians (who in the majority are Muslims) reveals a clear division between in-groups and out-groups. As the criteria for belonging to the in-group (on the national level) is indigenousness to the archipelago region; ethnic Chinese with their cultural Chinese features are thus perceived as members of the out-group. Ethnic Chinese, on the other hand, do not perceive an eclectic identity of being Chinese and Indonesian at the same time as problematic. Due to the different perceptions surrounding the Chinese Indonesia identity, indigenous Indonesians often doubt the loyalty of ethnic Chinese, while ethnic Chinese are not willing to give up on their Chineseness as it forms an integral part of their identity. Following the conflict analysis, possible approaches and measures for tackling the various dimensions and aspects of this conflict and putting these measures in practice according to the Transcend method are presented and discussed. Conflict transformation work in the case of the present conflict requires working towards a new social reality in which ethnic Chinese are no longer maintained in their marginalized position of middlemen and distinct others .

Im Mai 1998 kam es im Zuge des Regime-Sturzes Soehartos zu gewaltsamen Ausschreitungen der indigenen Mehrheitsbevölkerung Indonesiens. Ihr Unmut entlud sich nicht nur gegen die politischen Eliten, sondern vor allem gegen die ethnisch chinesische Minderheit. Diese Übergriffe markieren jedoch nicht den Beginn des Konflikts zwischen den indigenen Indonesiern und den ethnischen Chinesen, sondern sind Teil einer Konfliktentwicklung, die bis weit in die Kolonialzeit Indonesiens zurückreicht. Dieser Konflikt ist bis heute noch von Gewalt geprägt. Die vorliegende Arbeit unternimmt eine Konfliktanalyse hinsichtlich Austragungsform, Konfliktinhalt, Konfliktstruktur und Transformationspotential entlang der Forschungsfragen: Worum geht es in diesem Konflikt? Welche Strukturen erzeugen die teils gewaltsamen Spannungen zwischen den beiden asymmetrischen Konfliktparteien? Wie kann dieser Konflikt in einen nachhaltigen für alle Beteiligten akzeptablen Friedensprozess transformiert werden? Die vorliegende Analyse folgt der von dem Friedens- und Konfliktforscher Johan Galtung entwickelten Theorie und Methode zur Konfliktbearbeitung Transcend . Sie wird überwiegend in der praktischen Bearbeitung von Konflikten durch Mediatoren eingesetzt; für Konfliktstudien im Rahmen der akademischen Forschung wurde sie bisher selten genutzt. Mit der vorliegenden Fallstudie wird daher diese Methode an einem konkreten Fall zugleich auf ihre Anwendbarkeit geprüft. Für das Datenmaterial wird auf die einschlägige Literatur und auf Interviews zurückgegriffen, die die Verfasserin im Forschungszeitraum von 2008 bis 2010 in Indonesien geführt hat. Zunächst wird die Entwicklung der Konfliktformation Indonesiens bis in die Zeit des Soeharto-Regimes untersucht: In der Kolonialzeit schufen die Niederländer als Kolonialherren ein gesellschaftliches Gesellschaftssystem, das den ethnischen Chinesen eine Mittelstellung und zugleich gesellschaftliche Außenseiterrolle zwischen der niederländischen Elite und der indigenen Mehrheitsbevölkerung zuwies. Wie sich Gewalt in dieser Konfliktformation entwickelt hat und ob sie in der gegenwärtigen Zeit noch existiert, wird nach Galtungs Analyse-Schema des Gewaltdreiecks untersucht. Seit 1998 lässt sich eine Änderung der Gewaltqualität beobachten: Gewalttaten, die sich gegen ethnische Chinesen und ihr Eigentum richten, haben deutlich abgenommen, gleichwohl wird diese Bevölkerungsgruppe im Alltag nach wie vor benachteiligt und ausgegrenzt. Die Regierungen nach Soeharto haben zwar diskriminierende Gesetze abgeschafft, auch darf die öffentliche Entfaltung der kulturellen Identität der ethnischen Chinesen auf nationaler Ebene nicht mehr beeinträchtigt werden, doch auf regionaler Ebene finden sich immer noch (oder erneut) diskriminierende Verordnungen. Um Perspektiven für eine praktische Konfliktbearbeitung zu finden, wird die Konfliktformation mit Hilfe weiterer Analyse-Schemata Galtungs, dem Konfliktdreieck und dem Konflikttiefendreieck , untersucht. Die Konfliktparteien werden in dem Konfliktdreieck nicht als monolithische Blöcke betrachtet, sondern in Subgruppen unterteilt. Denn sowohl in der Bevölkerungsgruppe der ethnischen Chinesen als auch bei den indigenen Indonesiern gibt es Strömungen, die an der marginalisierten Stellung der ethnischen Chinesen innerhalb der indonesischen Gesellschaft aus unterschiedlichen Beweggründen festhalten, und solche, die eine Veränderung der gesellschaftlichen Struktur befürworten und aktiv unterstützen. Durch die Untersuchung der Tiefendimensionen des Konflikts werden unterschiedliche kulturelle Hintergründe und kollektive Traumata identifiziert, welche die jeweiligen Konfliktparteien in ihren Annahmen und ihrem Verhalten in Bezug auf den Konflikt unbewusst prägen. Die mehrheitlich muslimischen indigenen Indonesier etwa haben Schwierigkeiten, die ethnischen Chinesen mit ihrem spezifischen, für sie ausländischen kulturellen Erbe als gleichwertige Indonesier zu akzeptieren. Daher stellen sie deren Loyalität der indonesischen Nation gegenüber häufig in Frage. Die ethnischen Chinesen wiederum wollen auf die Auslebung ihrer kulturellen Identität nicht verzichten und möchten ihre Gruppenidentität nicht preisgeben. Im Anschluss an die Konfliktanalyse werden Möglichkeiten für die Praxis aufgezeigt, wie die verschiedenen Dimensionen und Aspekte des Konflikts im Zuge einer Konflikttransformation bearbeitet werden können. Dieser Teil der Arbeit orientiert sich an dem Bestreben, Wege zu zeigen, wie die gesellschaftlichen Verhältnisse dahingehend umgestaltet werden können, dass die ethnischen Chinesen ihre Außenseiterrolle ablegen können, um als vollständig akzeptierte und gleichberechtigte Mitglieder der Gesellschaft zu leben. Galtung hat verschiedene Methoden und Ansätze entwickelt und zusammengetragen, die eine Transformation der Gesellschaft bewirken bzw. anstoßen können, die hier in Bezug auf diese Fallstudie diskutiert werden.
Konfliktformation und Transformation in Indonesien: Chinesische und indigene Indonesier auf dem Friedensweg? : Eine Friedens- und Konfliktanalyse nach der Transcend-Methode
Keywords: ddc:320